Back Cover: Continuous Re‐hyperpolarization of Nuclear Spins Using Parahydrogen: Theory and Experiment (ChemPhysChem 12/2014). Issue 12 (25th August 2014) - Hövener, Jan‐Bernd; Knecht, Stephan; Schwaderlapp, Niels; Hennig, Jürgen; von Elverfeldt, Dominik
<x xml:space="preserve">Abstract</x> To demonstrate resolution down to 6 nm with the superresolution technique DNA PAINT, binding sites for fluorescent dyes are placed at different distances on top of DNA origami nanostructures, analogous to a macroscopic vision test. P. Tinnefeld et al. show on p. 2451 that distances down to 6 nm can be resolved with DNA PAINT. DNA origami can be used to prove this resolution as many identical structures allow statistical evaluation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>